A case report of a colouterine fistula treatment: when the patient chooses the steeplechase - Stefano Pontone; Pier Giorgio Nardis; Chiara Eberspacher; Domenico Mascagni (Annals of Coloproctology, 2023)
Colouterine fistula is a rare disease that is primarily treated using surgical approaches. Although invasive surgery is controversial in terms of techniques and results, minimally invasive endoscopic treatments have not been widely described. However, because it is rare for these fistulas to close spontaneously, surgical treatment is often mandatory. Appropriate management of colouterine fistula is complicated, especially when the patient refuses surgery. In this case study, we provide the first description of a minimally invasive endoscopic treatment of an iatrogenic colouterine fistula using a self-expandable metallic stent after an over-the-scope clip malposition.